Resolution of Viable and Membrane‐Compromised Free Bacteria in Aquatic Environments by Flow Cytometry. Issue 1 (29th June 2018) - Grégori, Gérald; Denis, Michel; Sgorbati, Sergio; Citterio, Sandra
Abstract: In aquatic environments, free heterotrophic bacteria play an extremely important role due to their high biomass, wide panel of metabolisms, and ubiquity, as well as the toxicity of certain species. This unit presents a nucleic‐acid double‐staining protocol (NADS) for flow cytometry that can distinguish fractions of viable, damaged, or membrane‐compromised cells within the free‐bacterial community. The NADS protocol is based on the simultaneous utilization of two nucleic acid stains—membrane‐permeant SYBR Green and membrane‐impermeant propidium iodide (PI). The efficiency of the double staining on fresh samples is magnified by the FRET from SYBR Green to PI when both are bound to the nucleic acids. Full quenching of SYBR Green fluorescence by PI identifies cells with a compromised membrane, partial quenching indicates cells with a slightly damaged membrane, and lack of quenching characterizes cells with an intact membrane. Samples do not require any pretreatment and this protocol can be performed almost anywhere. © 2018 by John Wiley & Sons, Inc.